Thermal Paper and Time Temperature Integrators Made From a Structural Colored Polymer Crosslinked With Hydrogen Bonded Cyclohexanoic Acid Derivatives. Issue 22 (24th August 2022) - Foelen, Yari; van der Heijden, Daniëlle A. C.; Verdurmen, Anne M. J.; Mulder, Dirk Jan; Lub, Johan; Schenning, Albert P. H. J.
Abstract: Hydrogen‐bonded cyclohexanoic derivatives are applied in a structural colored cholesteric liquid crystal (CLC) helical polymer that demonstrates an extraordinary dual thermal response. Integration of the dynamic hydrogen‐bonded cyclohexanoic acid derivatives in the CLC polymer as supramolecular crosslinks yields an immediate and irreversible loss of the green structural color upon exposure to temperatures above the cholesteric‐to‐isotropic transition temperature ( T NI ) caused by the helical order loss. Exposure to temperatures below the T NI yields a gradual irreversible red color shift of the reflected wavelength over broad temperature and time ranges. Most likely due to polymerization confinement in combination with the dynamics of the carboxylic acid hydrogen bonds, helical unwinding takes place over time causing the red shift of the reflected wavelength. The temperature response can be programmed by altering the chemical composition of the liquid crystal mixture. Furthermore, the green, structural color of the polymer can also be easily changed making it possible to print different colored indicators combined with different respective temperature responses on a single substrate. The printed optical sensors can be easily delaminated by dissolving the non‐covalent crosslinked polymer. Such optical polymer materials are attractive for easy processable time–temperature integrators and thermal paper. Abstract : Hydrogen‐bonded cyclohexanoic acid derivatives in a structural colored polymer demonstrate an extraordinary twofold thermal response: exposure to a temperature above the cholesteric‐to‐isotropic transition temperature ( T NI ) yields immediate and irreversible loss of color. Exposure below the T NI yields a time–temperature dependent color shift in a broad temperature range. This twofold thermal response permits applications as photonic thermal paper and as time–temperature integrators.